Fungsi Karawitan Bali Di Yogyakarta : Sebuah Tinjauan Kontekstual - I Ketut Ardana (Mudra Jurnal Seni Budaya, 2009)
Balinese gamelan music is an Indonesia traditional music which consist of pelog and selendro scales. The existence of Balinese gamelan music in Yogyakarta has an important function in its community. It marks by the significant development of it. The establishment of organization and Balinese gamelan groups indicate the devolopment. Balinese gamelan music uses by the Yogyanese, as good Balinese or native Yogyanese. Contextually, Balinese gamelan music in Yogyakarta has four functions, such as: ritual ceremonial, entertainment, esthetic presentation, and arts education. First, as a medium of a ritual ceremonial, Balinese gamelan music uses to accampany dewa yadnya, pitra yadnya, and buta yadnya. Second, Balinese gamelan music uses as an entertainment. Third, as an artistic presentation usually treated with some creativities and innovations. And the last but not least, Balinese gamelan music uses as course matrial at the Gamelan and Etnomusicology Departments at the Indonesia Institute Of The Arts at Yogyakarta.